2000
DOI: 10.1001/archinte.160.20.3128
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Inhaler and Nicotine Patch as a Combination Therapy for Smoking Cessation

Abstract: Treatment with the nicotine inhaler plus nicotine patch resulted in significantly higher cessation rates than inhaler plus placebo patch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 33 publications
1
99
1
3
Order By: Relevance
“…Thus, smoking cessation programs may benefit from including or adding additional counseling or support related to ways to improve mood and deal with stressors without smoking during the second week after a quit attempt. Unlike prior studies of longer term relapse (Blondal, Gudmundsson, Olafsdottir, Gustavsson, & Westin, 1999;Bohadana, Nilsson, Rasmussen, & Martinet, 2000;Kornitzer, Boutsen, Dramaix, Thijs, & Gustavsson, 1995;Piper et al, 2009;Smith et al, 2009), the two treatment groups did not differ significantly from each other. Thus, although this study provides some evidence for the impact of treatment over placebo, it does not provide strong evidence for choosing one type of therapy over another.…”
Section: Discussioncontrasting
confidence: 91%
“…Thus, smoking cessation programs may benefit from including or adding additional counseling or support related to ways to improve mood and deal with stressors without smoking during the second week after a quit attempt. Unlike prior studies of longer term relapse (Blondal, Gudmundsson, Olafsdottir, Gustavsson, & Westin, 1999;Bohadana, Nilsson, Rasmussen, & Martinet, 2000;Kornitzer, Boutsen, Dramaix, Thijs, & Gustavsson, 1995;Piper et al, 2009;Smith et al, 2009), the two treatment groups did not differ significantly from each other. Thus, although this study provides some evidence for the impact of treatment over placebo, it does not provide strong evidence for choosing one type of therapy over another.…”
Section: Discussioncontrasting
confidence: 91%
“…6 Bupropion/amfebutamone (Zyban) is an atypical antidepressant that has recently been approved as a medical therapeutic in smoking cessation. it avoids the hypertensive, cardiac, and other side effects of nicotine replacements.…”
Section: Diabetes Managementmentioning
confidence: 99%
“…10,18,20 In smoking-cessation therapy, an adequate dosage of NRT is important to control craving and withdrawal symptoms in order to prevent relapse. 18 It is reported that combination NRT treatment was superior to single NRT treatment in achieving one-year abstinence rates, 5,21 and that treatment duration had to be long enough to control symptoms that persisted several weeks after cessation. 22 Recently, it has been suggested that if a smoker was not able to stop smoking completely, sustained smoking reduction would be beneficial as it reduces exposure to tobacco smoke.…”
Section: Source Of Datamentioning
confidence: 99%
“…26 Studies have observed heterogeneity in nicotine withdrawal symptoms among smokers trying to stop smoking. 4,21 This variability in the pattern, severity and timing of withdrawal symptoms is important, as it could predict relapse after treatment. 27 This observed variability means that therapy to treat nicotine withdrawal symptoms should be individualised.…”
Section: Withdrawal Symptomsmentioning
confidence: 99%